Integration in social networks and perceived vulnerability to disease among high school students - Piotr Fedurek; Anna Szala; Tomasz Kulik; Dariusz P. Danel (Journal of Health Psychology, 2026)
Behavioural responses that limit social interactions can reduce infection risk and may operate through Perceived Vulnerability to Disease (PVD). Although social and environmental factors, such as population density and human mobility, influence PVD, little is known about how integration within proximity networks relates to perceived susceptibility. We examined measures of social integration, derived from friendship nominations and proximity sensor data, in relation to PVD among high school students. Friendship integration was based on within-class nominations, while proximity integration was assessed using sensors detecting classmates within 2 m. PVD was measured using self-report questionnaires. Integration measures were associated with PVD, but the direction differed by network type: greater proximity integration was associated with higher PVD, whereas greater friendship integration was associated with lower PVD. These findings highlight the relationship between social embeddedness and PVD, indicating that the number and quality of social ties are associated with variation in behavioural responses.